ANALYSIS OF NON-PERFORMING CREDIT POLICY AT BRI UNIT TOAYA - Irayanti, Estin (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2024)
This study aims to evaluate the credit quality managed by the BRI Unit Toaya and analyze its non-performing credit policies. The research employs a qualitative methodology with a descriptive approach. Primary data was collected through interviews with key credit debtors, complemented by observations. The findings reveal that the credit quality at the BRI Unit Toaya showed an upward trend from 2018 to 2022, maintaining its position within the healthy category. The non-performing credit policy at the BRI Unit Toaya involves restructuring measures, such as extending repayment periods and deferring principal and interest payments, tailored to the underlying causes affecting debtors, while adhering to the 5C criteria.